2010
DOI: 10.1007/s00216-010-3523-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of penicillins in porcine tissues, milk and animal feed using derivatisation with piperidine and stable isotope dilution liquid chromatography tandem mass spectrometry

Abstract: Penicillins are used universally in both human and veterinary medicine. The European Union (EU) has established maximum residue levels (MRLs) for most ß-lactam antibiotics in milk and animal tissues and included them in the National Residue Monitoring Programs. In this study, a novel method is described for the determination and confirmation of eight penicillins in porcine tissues, milk and animal feed by liquid chromatography–tandem mass spectrometry (LC–MS/MS). To prevent degradation of penicillin residues d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…No studies are known in which the effect of storage and storage temperature on the stability of PAs in animal matrices has been investigated. However, enzymatic degradation of residues in meat and liver tissues during storage is a well-known phenomenon for several classes of antibiotics, such as penicillins and tetracyclines (van Holthoon et al, 2010;Berendsen et al, 2011).…”
Section: Short-term Stability Of Pas In Meat Stored Under Retail Condmentioning
confidence: 99%
“…No studies are known in which the effect of storage and storage temperature on the stability of PAs in animal matrices has been investigated. However, enzymatic degradation of residues in meat and liver tissues during storage is a well-known phenomenon for several classes of antibiotics, such as penicillins and tetracyclines (van Holthoon et al, 2010;Berendsen et al, 2011).…”
Section: Short-term Stability Of Pas In Meat Stored Under Retail Condmentioning
confidence: 99%
“…As a result these should not be found in animal feeds. While there are single class methods for the analysis of some of compounds [Vincent et al, 2008;Galarini et al, 2009;Pecorelli et al, 2003;Barbosa et al, 2007;van Holthoon et al, 2010] [Dusi et al, 2000], amprolium/ethopabate [Tan et al, 1996] and carbadox [Kesiunaite et al, 2008;Hutchinson et al, 2005] while for compounds such as dinitolimide no a Dublin Institute of Technology,School of Chemical and Pharmaceutical Sciences,Kevin Street,Dublin 8,Ireland b State Laboratory,Young's Cross,Backweston Campus,Backweston,Celbridge,Co. Kildare,Ireland.…”
Section: Introductionmentioning
confidence: 99%
“…Although various analytical methods have been reported to detect and quantify antibiotics in milk (Mamani et al 2009;Gamba et al 2009;Rønning et al 2006;Kinsella et al 2009;Van Holthoon et al 2010;Santos et al 2007;Stolker et al 2008;Ortelli et al 2009;Nebot et al 2012), none of them have reported on the use of the QuEChERS method to extract milk for the detection and quantification of the particular antibiotics used in the present study.…”
Section: Introductionmentioning
confidence: 82%
“…Various multiclass methods have been reported to detect and quantify residues of veterinary drugs in milk. These include high-performance liquid chromatography with diode array detection (HPLC-DAD; Mamani et al 2009;Gamba et al 2009), liquid chromatography-tandem mass spectrometry (Rønning et al 2006;Kinsella et al 2009;Van Holthoon et al 2010), capillary electrophoresis (CE) coupled to a UV/Vis detector (Santos et al 2007), and ultra-performance liquid chromatography method combined with time-of-flight mass spectrometry (TOF-MS;Stolker et al 2008).…”
Section: Introductionmentioning
confidence: 99%